Modulation of the central carbon metabolism of Corynebacterium glutamicum improves malonyl-CoA availability and increases plant polyphenol synthesis - Milke, Lars (2019)
In recent years microorganisms have been engineered towards synthesizing interesting plant polyphenols such as flavonoids and stilbenes from glucose. Currently, low endogenous supply of malonylCoA, indispensable for plant polyphenol synthesis, impedes high product titers. Usually, limited malonylCoA availability during plant polyphenol production is avoided by supplementing fatty acid synthesisinhibiting antibiotics such as cerulenin, which are known to increase the intracellular malonylCoA pool as a side effect. Motivated by the goal of microbial polyphenol synthesis being independent of such expensive additives, we used rational metabolic engineering approaches to modulate regulation of fatty acid synthesis and flux into the citric acid cycle in Corynebacterium glutamicum strains capable of flavonoid and stilbene synthesis. Initial experiments showed that sole overexpression of genes coding for the native malonylCoAforming acetylCoA carboxylase is not sufficient for increasing polyphenol production in C. glutamicum. Hence, the intracellular acetylCoA availability was also increased by reducing the flux into the citric acid cycle through reduction of citrate synthase activity. In defined cultivation medium, the constructed C. glutamicum strains accumulated 24 mg/L (0.088 mM) naringenin or 112 mg/L (0.49 mM) resveratrol from glucose without supplementation of phenylpropanoid precursor molecules or any inhibitors of fatty acid synthesis.